2014
DOI: 10.1055/s-0040-1703731
|View full text |Cite
|
Sign up to set email alerts
|

Serum Antibody Analysis Following Hepatitis B Vaccination for Occupational Risk Assessment Among Dental Students

Abstract: Background & Objectives: Hepatitis B is the most important infectious occupational disease for the health care workers. Dental surgeons are frequently in contact with blood and saliva and hence are at high risk for Hepatitis B Virus (HBV) exposure. HBV infection is a major public health problem in India, as there are 45 million estimated carriers. Immunization against HBV reduces the risk of transmission of HBV to dental personnel and from dental personnel to patients. The present study was aimed to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 30 publications
0
4
1
Order By: Relevance
“…The fact observed in this study that Smoking of tobacco is not significantly associated with low level of anti-HBs IgG has been in discordance with studies of Shruti Hegde et al [18] from Karnataka in South India and Lakshmanan et al [14] from Agartala in North east India as they have found smoking to be a significant attribute for low levels of anti-HBs IgG titer in medical students and health care workers respectively.…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…The fact observed in this study that Smoking of tobacco is not significantly associated with low level of anti-HBs IgG has been in discordance with studies of Shruti Hegde et al [18] from Karnataka in South India and Lakshmanan et al [14] from Agartala in North east India as they have found smoking to be a significant attribute for low levels of anti-HBs IgG titer in medical students and health care workers respectively.…”
Section: Discussioncontrasting
confidence: 86%
“…Unlike the study of Shruti Hegde et al [18] in dental students of Mangalore and that of Syed Rahamathulla et al [15] in vaccinated doctors in Andhra Pradesh where male gender has been attributed to low anti-HBs titer, no such statistically significant gender predilection has been found with low anti HBs IgG in our study Anti-HBs IgG titer has been said to wane with time elapsed after vaccination and so has been found in our study where passage of >10 years post vaccination has been found to have been significantly associated with inadequate protective anti-HBs. Similar observation has been made in the study of Dr V K Kataria et al [16] in their study on healthcare professionals from New Delhi.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…(1) Gender based information in the present study revealed higher immunity in females 114 (77.55%) compared to males 79 (65.28%), similar to studies of Ganczak (79.5%), Chathuranga and Shruthi hedge. (11,8,12) According to Varsha singhal, 5-10% of the adult population will not respond to standard HBV vaccination. (13) Risk factor for vaccine nonresponse include: male sex, older age, cigarette smoking, obesity, immunodeficiency, chronic diseases, certain HLA halotypes ,celiac disease, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Inclusion criteria was vaccinated persons and exclusion criteria was non vaccinated persons. Doctors (113), medical and nursing students (62), nurses (59), technicians (15), group D workers (12) and others (07) formed the study group. Age, gender, occupation and details of vaccination schedule of each individual (dose and duration) were taken.…”
Section: Methodsmentioning
confidence: 99%